THE MOST IMPORTANT TASKS OF DEVELOPMENT OF A REGIONAL TEACHERS’ TRAINING - Sergey P. Shilov (Высшее образование в России)
The article deals with the main problems, priority directions and means of improving the process of training future pedagogues in a regional higher educational institution.